Nitrous oxide and methane emissions from a subtropical rice–rapeseed rotation system in China: A 3-year field case study - Minghua Zhou; Bo Zhu; Bruggemann, N.; Xiaoguo Wang; Xunhua Zheng; Butterbach-Bahl, Klaus (Elsevier, 2015)
Fertilizer nitrogen (N) application has been shown to impact both methane (CH4) and nitrous oxide (N2O) emissions from rice-based crop systems, yet the responses of CH4 and N2O fluxes to N fertilizer applications in subtropical rice–rapeseed rotation systems are not well documented. A three-year field experiment was conducted to simultaneously measure the fluxes of CH4 and N2O from a subtropical rice–rapeseed rotation system under three N fertilization treatments (control with no N fertilizer addition [CK], optimized N fertilizer management practice in accordance with the recommended N fertilizer application rate of 150 kg N ha−1 season−1 [OP], local farmers common N fertilizer management practice with 250 kg N ha−1 season−1 [CP]) in southwestern China. Results showed great intra- and inter-annual variations in CH4 and N2O emissions along with the temporal variations of environmental conditions, emphasizing the necessity of multi-year measurements to achieve representative estimates. Nitrogen fertilization tended to increase N2O emissions and to inhibit CH4 emissions. The direct N2O emission factors (EFd) for the rice systems (mean: 0.99%) were higher than those for the rapeseed systems (mean: 0.71%). In addition, the rice-growing season dominated annual CH4 emissions (>97%), which on average represented 87% of the annual total global warming potential (GWP) of CH4 and N2O emissions across experimental treatments and years. Linking total GWP of CH4 and N2O emissions with grain yields, the average annual yield-scaled GWP for the control (1467 kg CO2-eq Mg−1 grain) was significantly higher than for the OP (700 kg CO2-eq Mg−1 grain) and CP (682 kg CO2-eq Mg−1 grain) treatments (P < 0.05). Given the comparable area- and yield-scaled GWP between the CP and OP treatments, the OP treatment reduced local farmers’ common N fertilizer application rate by 40% and tended to maintain crop grain yields, however it also reduced N surplus and off-site N losses in the subtropical rice–rapeseed rotation systems of southwestern China.